Pain Perception Modulates Synaptic and Somatic Plasticity in the Dentate Gyrus of Rats - Soley Arslan; Esra Tufan; Hacer Balkaya; Buse Günaydın Türker; Sebahat Melike Durukan; Ayşenur Çimen; Cem Süer (International Journal of Pain Management, 2024)
An experimental study examines how pain perception alters synaptic and somatic plasticity in the dentate gyrus. It summarizes methods, key electrophysiological findings, and implications for pain‑related cognitive effects.
Keywords: Dentin Erosion